Peer Effects in Alcohol Consumption: Evidence from Russia's Beer Boom - Koen Deconinck; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
Starting around 1996, Russia witnessed a strong growth in beer consumption, leading to a fivefold growth in average beer consumption and making beer the most important alcoholic drink today. We use survey data from the Russian Longitudinal Monitoring Survey (RLMS) to analyze individual detfirminants of beer drinking. Using both lagged and simultaneous measures to establish lower and upper bounds on the peer effect, we show that the decision to drink beer is strongly influenced by the average behavior of the individual's peer group. We find that this peer effect may account for one-third to one-half of the rise of beer in Russia.
Keywords: I12; D12; 330; peer effects; Russia; alcohol; beer consumption; dynamic linear probability model